An Introduction to Tensor Analysis - Koranga, Bipin Singh (River Publishers, 2020)
This is a short introduction to the topic of Tensor Analysis. A tensor is an entity which is represented in any coordinate system by an array of numbers called its components. The components change from coordinate system to coordinate in a systematic way described by rules. The arrays of numbers are not the tensor; they are only the representation of the tensor in a particular coordinate system. The special properties of tensors are important for solving problems in Physics and Geometry.